1994
DOI: 10.7773/cm.v20i2.965
|View full text |Cite
|
Sign up to set email alerts
|

Daily variations of temperature, salinity, dissolved oxygen and chlorophyll a, in a hypersaline lagoon of the Gulf of California

Abstract: Se obtuvieron series de tiempo durante un año para temperatura. salinidad, oxígeno disuelto y clorofila n, en un punto tijo de la laguna La Cruz, Sonora (México), con la finalidad de conocer los procesos que generan variación en la laguna. El análisis espectral de estas series indica que las frecuencias de variación están asociadas con procesos de 3 a 15 días. Los procesos quincenales están relacionados con mareas vivas y muertas. mientras que los de tres días son debidos a efectos del viento yio diferencias p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
1
2
0
2
Order By: Relevance
“…Feeding of pen shells is affected by variations in concentrations of POM and PIM (Safi et al 2007); for example, a strong relationship between tissue growth and availability of food, as measured by organic seston matter, has been documented in P. carnea (Narváez et al 2000). Although seston as well as concentrations of chlorophyll a at our study site showed similar ranges as those reported in other lagoons of the region (Valdez‐Holguín 1994; Barrios‐Ruíz et al 2003), no correlation of these parameters with the measurements of somatic growth was detected in our study. Nevertheless, the concentration of seston and chlorophyll may suggest that availability of food was not a limiting factor for growth of A. maura .…”
Section: Discussionsupporting
confidence: 72%
“…Feeding of pen shells is affected by variations in concentrations of POM and PIM (Safi et al 2007); for example, a strong relationship between tissue growth and availability of food, as measured by organic seston matter, has been documented in P. carnea (Narváez et al 2000). Although seston as well as concentrations of chlorophyll a at our study site showed similar ranges as those reported in other lagoons of the region (Valdez‐Holguín 1994; Barrios‐Ruíz et al 2003), no correlation of these parameters with the measurements of somatic growth was detected in our study. Nevertheless, the concentration of seston and chlorophyll may suggest that availability of food was not a limiting factor for growth of A. maura .…”
Section: Discussionsupporting
confidence: 72%
“…and biological (e.g. the balance between photosynthesis and respiration) phenomena [26] , [27] . Further investigation into the physical characteristics of the natural hypersaline environment of halophilic archaea provided clues into the potential implication of light-mediated entrainment of oxygen-associated physiologies.…”
Section: Resultsmentioning
confidence: 99%
“…Dado que el crecimiento de los juveniles en los sitios de producción coincide con las temperaturas extremas, el equilibrio fisiológico de los ostiones puede verse amenazado. Además, las variaciones de temperatura a su vez afectan otras variables hidrológicas estacionales, especialmente la biomasa fitoplanctónica (Valdez-Holguín 1994). No se sabe con precisión la importancia relativa de la temperatura y la disponibilidad de alimento sobre el crecimiento y la condición de los ostiones, en particular durante las etapas juveniles (Barraza-Guardado et al 2008).…”
Section: Experimental Design and Samplingunclassified
“…Las semillas de la especie nativa y la introducida son transportadas a los cultivos comerciales durante los mismos periodos, pero no se han hecho estudios en que se hayan comparado directamente crecimiento, rendimiento y supervivencia de ambas especies. Sorprendentemente, existe poca información sobre los efectos de las variaciones ambientales de factores abióticos y bióticos sobre el crecimiento y la supervivencia que for other seasonal hydrological fluctuations, especially that of phytoplankton biomass (Valdez-Holguín 1994). The relative importance of temperature and food availability for the growth and condition of oysters, particularly during juvenile stages, is not precisely understood (Barraza-Guardado et al 2008).…”
Section: Introductionunclassified